STUDI PENGALAMAN GURU-GURU MTSN 6 PESISIR SELATAN DALAM PENULISAN KARYA TULIS ILMIAH GUNA MENINGKATAN IPTEK MASYARAKAT SERTA MEWUJUDKAN GURU YANG PROFESIONAL - Fanny Rahmatina Rahim; Festiyed Festiyed; Yohandri Yohandri; Yulkifli Yulkifli; Djusmaini Djamas (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
Teachers have an important role in education. To support it, teachers should have good profess sionalism especially in writing articles. In fact, many teachers are not proficient in writing articles because they do not have enough knowledge about it. Teachers need such training for increasing their experience in writing. After that, the progress will be seen. The research method is descriptive quantitative. The data in this research is quantitative data. The type of data is the primary data. A data collection technique in this study is questionnaires. Data processing techniques used include editing, coding, tabulation, and scoring. Data analysis technique is descriptive analysis percentage. After doing the training, the teachers have more knowledge and interest of writing articles.